Clinical ethics and patient centred communication: evidence based application through an educational perspective - Sami Mohamed (Future Healthcare Journal)
Background: Clinical ethics deals with ethical issues in clinical practice scoped through the four ethical principles, alongside professional communication, to uphold good medical practice. This study aimed to emphasise the educational significance of patient-centred healthcare communication in clinical ethics, utilising classical, novel and technology-based approach models. Methods: An in-depth comprehensive review was carried out of sources focusing on recent systematic reviews and randomised controlled trials obtained by searching Scopus, Web of science, PubMed and Google Scholar databases. Discussion: Effective healthcare communication incorporates patient centredness using verbal and non-verbal techniques. Emerging technologies influenced by the pandemic including use of video conferences, chatbots, AI and virtual reality in communication, impacted participants' satisfaction, signifying transformative innovation in medical education. Ethical issues approaches including ICE for counselling, SPIKES for breaking bad news, SDM for informed consents, DNAR orders for medical futility, de-escalation tactics for anger and a combined approach for disasters, were found to be effective through patient-centred communication. Conclusion: Highlights of the study include: (1) patient-centred healthcare communication acts as a vessel for clinical application of the intertwined clinical ethics; (2) advances in telehealth communication, online instrumental application, AI and virtual reality technology have potential impact on patient outcomes and satisfaction; (3) simulation-based education for health professionals strengthens healthcare providers' confidence during complex ethical encounters; (4) the application and evaluation of classical models, including ICE and SPIKES, provides a foundation for the development of novel evidence-based ethical approaches; and (5) challenging ethical issues pertaining to end-of-life care (Fig 1), adverse events (Fig 2), anger and disasters require team-based patient centred communication.Ethical issues require implementation of systematic or technology evidence-based approaches that utilise contextually tailored patient-centred communication, built upon learner-centred health professions education. Engagement in patient-centred communication education requires institutional support, strengthened through the development of innovative simulation-based educational strategies. However, further outcome-based studies on telehealth and AI are still needed.